Manipulation erzeugt bei chronischem LBP ähnliche Verbesserungen wie andere empfohlene Therapien - Vielitz, Arne (manuelletherapie, 2020)
Rubinstein SM, de Zoete A, van Middelkoop M et al. Benefits and Harms of Spinal Manipulative Therapy for the Treatment of Chronic Low Back Pain: Systematic Review and Meta-analysis of Randomised Controlled Trials. BMJ 2019; 364: l689. doi: 10.1136/bmj.l689